O papel das quimiocinas CCL3, CCL2 e seus receptores na movimentação dentária ortodôntica - Silvana Rodrigues de Albuquerque Taddei (2011)
Orthodontic tooth movement (OTM) is achieved by the remodeling of periodontal ligament (PDL) and alveolar bone in response to mechanical loading. This process is regulated by pro-inflammatory mediators, such as cytokines and chemokines. CCL2, CCL3 and CCL5 are chemokines involved in osteoclastogenesis and are upregulated in periodontium after mechanical loading. As their cellular effects are mediated by binding to receptors, this study aimed to investigate the role of the chemokines and receptors CCL3/CCR1/CCR5 and CCL2/CCR2 in osteoclast recruitment and activation during OTM. An orthodontic appliance was placed in wild-type mice (WT), CCR5-deficient mice (CCR5-/-), CCR1-deficient mice (CCR1-/-), CCL3-deficient mice (CCL3-/-), CCR2-deficient mice (CCR2-/-) and mice treated with Met-RANTES (antagonist of CCR1 and CCR5), P8A (analog of CCL2) and vehicle (PBS). The number of TRAP-positive osteoclasts and the amount of OTM were quantified histomorphometrically. Moreover, the expression of mediators involved in bone remodeling was evaluated by Real-time PCR. Our data showed that the number of TRAP-positive cells, the amount of OTM and RANKL, Cathepsin K and MMP13 levels were significantly higher in CCR5-/- compared to WT mice. On the other hand, the number of osteoclasts and the amount of OTM were significantly diminished in CCL3-/- mice, CCR1-/- mice and Met-RANTES treated mice when compared to WT and vehicle treated mice, respectively. In accordance with these results, the levels of RANK, RANKL and TNF- decreased in CCL3-/- mice. Moreover, the treatment with Met-RANTES also reduced the expression of Cathepsin K and MMP13. These results suggest that CCR1 is one of the main pro-resorbing chemokine receptors, while CCR5 is an anti-resorbing receptor involved in OTM. In addition, the CCR1 action is dependent, at least in part, on CCL3 binding. Furthermore, TRAP-positive cells and the amount of OTM were significantly decreased in CCR2-/- and P8A-treated mice, when compared to WT and vehicle treated mice, respectively. In agreement with these data, the expression of the RANKL/RANK axis was lower in CCR2-/- than in WT mice. In summary, our results suggest that the CCL2/CCR2 axis might be involved in osteoclast activity and recruitment during OTM